2014
DOI: 10.1177/00333549141291s209
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Racial/Ethnic Diversity in Nursing to Reduce Health Disparities and Achieve Health Equity

Abstract: As nursing continues to advance health care in the 21st century, the current shift in demographics, coupled with the ongoing disparities in health care and health outcomes, will warrant our ongoing attention and action . As within all health professions, concerted efforts are needed to diversify the nation's health-care workforce . The nursing profession in particular will be challenged to recruit and retain a culturally diverse workforce that mirrors the nation's change in demographics . This increased need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
150
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(155 citation statements)
references
References 14 publications
1
150
0
4
Order By: Relevance
“…Other approaches to improving nursing workforce diversity are addressed in other articles in this supplement. [24][25][26] Improving the diversity of the health services research workforce is equally important. AHRQ grants support the conduct of health services research and the training and development of health services researchers.…”
Section: Tracking Workforce Diversitymentioning
confidence: 99%
“…Other approaches to improving nursing workforce diversity are addressed in other articles in this supplement. [24][25][26] Improving the diversity of the health services research workforce is equally important. AHRQ grants support the conduct of health services research and the training and development of health services researchers.…”
Section: Tracking Workforce Diversitymentioning
confidence: 99%
“…Despite the need to increase the number of Latino nurses to meet the growing need, only 6.8% of students registered in nursing programs across the United States identify as Latino (Alvarez, 2012). Studies have consistently documented that patient-nurse race and ethnic concordance is linked with higher patient satisfaction and increased health care outcomes (Phillips, J & Malone, B, 2014). Additionally, it has been noted in the literature that racial, ethnic and language concordance will improve patient provider communication, tolerance, and trust, decision-making, and improve health outcomes (Gonzalez-Guarda, R, Hassmiler, S, 2011).…”
Section: Problemmentioning
confidence: 99%
“…In order to obtain Latino nurses, Latino students must be recruited and retained in nursing programs. Historically, high attrition rates have been a significant concern for completion rates of nursing programs for Latinos (Phillips, J & Malone, B, 2014). The Institute of Medicine (IOM) in collaboration with the Robert Wood Johnson Foundation (RWJF) established a major initiative in July 2009, on the future of Nursing: Implications for Hispanic Nurses (Gonzalez-Guarda, R, Hassmiler, S, 2011).…”
Section: Needmentioning
confidence: 99%
“…For example, participants in this body of research have recommended that changes be woven throughout the curriculum and institution, not addressed solely in a single course on racism or health disparities . Nursing scholars have also concluded that gaps in current curricula cannot be overcome by simply incorporating a stand‐alone module about social inclusion . Because midwifery education programs are embedded in the dominant culture of the United States, they have been shaped by institutionalized racism and implicit bias, both of which are pervasive and often invisible to participants
in these institutions .…”
Section: Introductionmentioning
confidence: 99%